Metode Deskripsi Untuk Mengetahui Pola Belanja Konsumen Pada Data Penjualan - Wahju Tjahjo Saputro (Universitas Muhammadiyah Purworejo, 2020)
Internet technology is one part of information technology. The internet can make it easy for anyone to obtain large amounts of data. The abundance of data raises the question of What knowledge can be generated from this data or information?. To gain knowledge from the abundant chunks of data, it can be solved by the method described in the data mining field. The description method is used to describe and describe the patterns of consumer spending. Sales data always has a high number of transactions every day. This large amount of transaction data can be found in the knowledge of the patterns of goods being sold. Data mining has many methods or algorithms that can explore various knowledge. This study seeks to find patterns in consumer transaction data using descriptive methods using Borland Delphi 7.0 and MySQL database. The results of this study can display knowledge-based information in the form of information on average values, mean values, mode values, levels of data diversity, and graphs.